FREQUENCY OF DETACHED CARDIAC DRUGS PRESCRIBING IN PATIENTS OF DIFFERENT CLASSES QRS COMPLEX DURATION ON THE PERMANENT PACING BACKGROUND - Shanina, I. V.; Volkov, D. E. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
The frequency of beta-blockers, amiodarone, antiplatelet agents (acetylsalicylic acid), anticoagulants (warfarin), statins, angiotensin-converting enzyme inhibitors, diuretics and angiotensin II receptor antagonists prescribing was determined in 114 patients (56 – women, 58 – men) with permanent pacemakers in VVI/VVIR (40 patients), DDD/DDDR (26 patient), cardiac resynchronization therapy (14 patients) and separate group was made up of 34 patients with sinus sick syndrome in DDD/DDDR pacing mode in 3 QRS complex duration classes: 1 – under 119 ms (normal), 2 – 120-149 ms (elongate) and more than 150 ms (significantly elongate). The patients’ average age was 69 ± 7 years. The results showed that the same groups of drugs are being prescribed as in patients with pacemakers as in patients without them. More frequent prescribing of beta-blockers was associated with prevention of the development of possible device-induced arrhythmias and chronic heart failure. More rare appointment acetylsalicylic acid and statins was associated with the lack of attention to therapeutic support. Frequency of prescribing most of used drugs in patients with implanted pacemaker increases with QRS complex duration class.